2005
DOI: 10.1177/1054773804271936
|View full text |Cite
|
Sign up to set email alerts
|

Happiness as Related to Gender and Health in Early Adolescents

Abstract: The purposes of this study were to examine gender differences in happiness; to examine the relationship between happiness and several health variables, such as perceived health status, clinical health, and wellness, in early adolescents; and to examine further these relationships for boys and girls separately. The final sample consisted of 151 early adolescent boys and girls who were in the seventh and eighth grades of an urban middle school. Students responded to instruments measuring happiness, perceived hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 22 publications
6
32
1
5
Order By: Relevance
“…The SWB of eighth grade students in Turkey did not vary with gender similar to published literature (Ben-Zur, 2003;Çevik, 2010;Diener, 1984;Diener, Such, Lucas & Smith, 1999;Eken, 2010;Kartal, 2013;Katja, Paiva, Marja, Terttu & Pekka, 2002;Mahon, Yarcheski & Yarcheski, 2005;Nigar, 2014;Özen, 2005;Tuzgöl-Dost, 2004;Tuzgöl-Dost, 2006). This could be attributed to developmental characteristics of schoolgirls and boys in this agegroup (Çelik, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…The SWB of eighth grade students in Turkey did not vary with gender similar to published literature (Ben-Zur, 2003;Çevik, 2010;Diener, 1984;Diener, Such, Lucas & Smith, 1999;Eken, 2010;Kartal, 2013;Katja, Paiva, Marja, Terttu & Pekka, 2002;Mahon, Yarcheski & Yarcheski, 2005;Nigar, 2014;Özen, 2005;Tuzgöl-Dost, 2004;Tuzgöl-Dost, 2006). This could be attributed to developmental characteristics of schoolgirls and boys in this agegroup (Çelik, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…This relationship was also found in adolescents 64 , the young 65,66 and the elderly 67 . However, in the elderly, a study found that health predicted subjective well-being, but the reverse was not true 68 , perhaps because, in this population, other factors previously listed in the sociodemography of happiness subsection 3,4 came into play.…”
Section: Health Mental Health and Happinesssupporting
confidence: 54%
“…Some authors [5,11,12] think that this different externalisation/internalisation patterns is responsible for showing different symptoms, and in particular for bringing more symptoms and less perceived well-being for girls. The same and other authors [5,6,19] also suggest that these different patterns could constitute a bias in the measurement of well-being for boys and girls: in fact, we usually evaluate people's well-being more on the basis of symptoms than on actions and this can lead to an over estimation of the difference between the genders. Anyway Mincowsky and Ross [19] controlled the difference in the health status between boys and girls for their different tendency to internalise and externalise, and found that this factor cannot completely account for this difference.…”
Section: Discussionmentioning
confidence: 85%
“…This situation seems to start very early in the life course [2][3][4][5], and that some evidence of this gap may be seen already in adolescence. However, some researchers found doubtful results on this issue [6], also because large scale, cross-country results giving evidence on this fact are not common.…”
Section: Introductionmentioning
confidence: 99%